2023
DOI: 10.47197/retos.v50.97742
|View full text |Cite
|
Sign up to set email alerts
|

Actividad física de cuerpo y mente. Pilates y yoga. Efectos en la vitalidad y salud mental. Revisión sistemática y metaanálisis (Physical activity of body and mind. Pilates and yoga. Effects on vitality and mental health. Systematic review and meta-analysis)

Mario Manuel López Mesa,
Cristina Cagüe Fernández,
Diego Flández Santos

Abstract: El objetivo principal de esta revisión es analizar los efectos de los ejercicios de Pilates y yoga en la vitalidad y salud mental, utilizando la escala de calidad de vida SF-36. Se realizó una exhaustiva búsqueda en las bases de datos de Pubmeb, PEDRo, Scopus, Scielo, Google Scholar y WorldWideScience, identificando un total de 169 artículos. Después de llevar a cabo los procesos de selección, elegibilidad e inclusión, se seleccionaron 20 artículos (11 de Pilates, 8 de yoga y 1 con intervención de Pilates y yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
(125 reference statements)
0
0
0
Order By: Relevance
“…Both respondents revealed that they were interested in freediving to calm their minds, self-control and through a type of breathing exercise in freediving which is similar to yoga plus the presence of dynamic apnea swimming which makes the body relax and feel happy. In line with other research López Mesa et al,( 2023) that yoga exercises on effectiveness of yoga exercises as physical therapy in moderately improving quality of life in terms of vitality and mental health. Research studies have shown a noteworthy impact an activities related to yoga, such as pranayama breath-hold training, hata-vinyasa yoga practice there was a significant improvement in breath-holding capacity (Barrientos et al, 2021;Singh et al, 2022;Patel, 2021;Saoji et al, 2018;Rai, 2014;Durai & Athisayaraj, 2019;Vigneshwaran, 2015) Freediving Sport Engagement As A Learning Journey Learning the recreational sport of freediving and interpreted as a main task in the activity of adding knowledge and skills within the framework of a learning journey.…”
Section: Freediving Recreational As a Healthy Physical Activitysupporting
confidence: 87%
“…Both respondents revealed that they were interested in freediving to calm their minds, self-control and through a type of breathing exercise in freediving which is similar to yoga plus the presence of dynamic apnea swimming which makes the body relax and feel happy. In line with other research López Mesa et al,( 2023) that yoga exercises on effectiveness of yoga exercises as physical therapy in moderately improving quality of life in terms of vitality and mental health. Research studies have shown a noteworthy impact an activities related to yoga, such as pranayama breath-hold training, hata-vinyasa yoga practice there was a significant improvement in breath-holding capacity (Barrientos et al, 2021;Singh et al, 2022;Patel, 2021;Saoji et al, 2018;Rai, 2014;Durai & Athisayaraj, 2019;Vigneshwaran, 2015) Freediving Sport Engagement As A Learning Journey Learning the recreational sport of freediving and interpreted as a main task in the activity of adding knowledge and skills within the framework of a learning journey.…”
Section: Freediving Recreational As a Healthy Physical Activitysupporting
confidence: 87%